Islam and Muslim Life in West Africa Practices, Trajectories and Influences - Chappatte, André; Sounaye, Abdoulaye (ZMO-Studien, 2022)
The book offers an examination of issues, institutions and actors that have become central to Muslim life in the region. Focusing on leadership, authority, law, gender, media, aesthetics, radicalization and cooperation, it offers insights into processes that reshape power structures and the experience of being Muslim. It makes room for perspectives from the region in an academic world shaped by scholarship mostly from Europe and America.